2014
DOI: 10.3906/vet-1404-61
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant supplementation and purification of semen for improved artificial insemination in livestock species

Abstract: Improving sire reproductive performance in artificial insemination (AI) programs and maximizing the use of sires with valuable genomes are high on the list of priorities for livestock breeders in the United States and worldwide. While fixed-time AI and accurate estrous detection have already ameliorated the reproductive management of cows and sows, substantial gains remain to be made in the selection and utilization of male animals for field AI. In addition to better, more objective evaluation of breeding soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 136 publications
1
40
0
2
Order By: Relevance
“…bactericidal and growth promoting)- little in vivo evidence to support many internal applications demonstrated in vitro- cytotoxicity[31–34, 44, 45, 85, 86]Future applications Nutraceuticals- increased nutrient bioavailability- extra support for weanlings- growth and performance enhancement- solution for nutrient deficiencies- nanoparticles must be not be degraded in the GI tract before absorption in the intestines[27, 38, 4752, 59] Nutrient delivery systems- increased nutrient bioavailability- extra support for weanlings- growth and performance enhancement- carrier system must be designed to withstand GI tract challenges- bioaccumulation- biocompatibility concerns[21, 26] Therapeutics- alternatives to antibiotics- enhanced pathogen/organ targeting- biocompatibility considerations- efficacy against different pathogens- relative MIC[41–43, 53] Drug delivery systems- platforms to enhance drug specificity and delivery- reduce MIC and kill antibiotic-resistant strains of pathogens- biocompatibility considerations- potential for bodily accumulation- confidence in specificity[61, 62, 6567] Medical Imaging- additional modes of tracing organ systems and tracking drug therapies in the body- depth of tissue- biocompatibility considerations[61, 62, 65] Nanopurification of sperm- isolate desired sperm based on biomarkers (i.e. healthy from unhealthy)- increase fertilization efficiency, more females fertilized from a single collection- biomarker library to be developed- purebred restrictions on artificial insemination[75, 76, 83, 84] Cryopreservation of sperm- sperm preserved for longer- protecting against freeze-thaw cycles- to replace antibiotics from extenders; lower risk of reduced sperm motility- spermatotoxicity- oocyte toxicity[7680, 83, 84] Genetic manipulation- can carry DNA of interest from cytoplasm into cell nucleus- benefits to sperm-mediated gene transfer approach...…”
Section: Applications Of Nanotechnologymentioning
confidence: 99%
“…bactericidal and growth promoting)- little in vivo evidence to support many internal applications demonstrated in vitro- cytotoxicity[31–34, 44, 45, 85, 86]Future applications Nutraceuticals- increased nutrient bioavailability- extra support for weanlings- growth and performance enhancement- solution for nutrient deficiencies- nanoparticles must be not be degraded in the GI tract before absorption in the intestines[27, 38, 4752, 59] Nutrient delivery systems- increased nutrient bioavailability- extra support for weanlings- growth and performance enhancement- carrier system must be designed to withstand GI tract challenges- bioaccumulation- biocompatibility concerns[21, 26] Therapeutics- alternatives to antibiotics- enhanced pathogen/organ targeting- biocompatibility considerations- efficacy against different pathogens- relative MIC[41–43, 53] Drug delivery systems- platforms to enhance drug specificity and delivery- reduce MIC and kill antibiotic-resistant strains of pathogens- biocompatibility considerations- potential for bodily accumulation- confidence in specificity[61, 62, 6567] Medical Imaging- additional modes of tracing organ systems and tracking drug therapies in the body- depth of tissue- biocompatibility considerations[61, 62, 65] Nanopurification of sperm- isolate desired sperm based on biomarkers (i.e. healthy from unhealthy)- increase fertilization efficiency, more females fertilized from a single collection- biomarker library to be developed- purebred restrictions on artificial insemination[75, 76, 83, 84] Cryopreservation of sperm- sperm preserved for longer- protecting against freeze-thaw cycles- to replace antibiotics from extenders; lower risk of reduced sperm motility- spermatotoxicity- oocyte toxicity[7680, 83, 84] Genetic manipulation- can carry DNA of interest from cytoplasm into cell nucleus- benefits to sperm-mediated gene transfer approach...…”
Section: Applications Of Nanotechnologymentioning
confidence: 99%
“…Using of natural origin antibiotics (as propolis) instead of synthetic antibiotic in ram semen preservation is interesting in the recent years. Petruska et al (2014) suggested that propolis had an extensive span of biological activities including antibacterial, antiviral, anti-inflammatory and antioxidant properties. Moreover, Akandi et al (2015) proved that propolis in semen medium could protect some semen characteristics as motility, viability and DNA integrity.…”
Section: -Effect Of Synthetic and Natural Antibiotics In The Extendementioning
confidence: 99%
“…Antioxidants and other ROS scavengers potentially suitable as semen extender supplements include glutathione, resveratrol and related grape flavonoids, plant and berry extracts, honey bee and propolis compounds, and vitamins [reviewed in Petruska et al. ()]. In boars, glutathione and cysteine supplementation improved sperm viability, acrosomal integrity and in vitro fertilizing ability of extended, cooled semen (Funahashi and Sano ).…”
Section: Technologies For the Improvement Of Ai Dosementioning
confidence: 99%
“…Fertility of the extended and even sex-sorted boar semen could be further ameliorated by supplementation with antioxidants to compensate for the loss of sperms' natural antioxidant activities during boar semen freezing and storage (Gadea et al 2004;Bathgate 2011;Xia et al 2012). Antioxidants and other ROS scavengers potentially suitable as semen extender supplements include glutathione, resveratrol and related grape flavonoids, plant and berry extracts, honey bee and propolis compounds, and vitamins [reviewed in Petruska et al (2014)]. In boars, glutathione and cysteine supplementation improved sperm viability, acrosomal integrity and in vitro fertilizing ability of extended, cooled semen (Funahashi and Sano 2005).…”
Section: Technologies For the Improvement Of Ai Dosementioning
confidence: 99%
See 1 more Smart Citation